Active energy ray-curable composition for forming hard coat layer, hard coat film using same, and laminate thereof

JP2025036009APending Publication Date: 2025-03-14TOYO INK MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024008018
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2025-03-14

Smart Images

  • Figure 2025036009000001
    Figure 2025036009000001
  • Figure 2025036009000002
    Figure 2025036009000002
  • Figure 2025036009000003
    Figure 2025036009000003
Patent Text Reader

Abstract

To provide an active energy ray-curable composition for forming a hard coat layer that protects a display section from external ultraviolet rays, enhances white clarity, prevents scratches during the production process, prevents curling due to curing shrinkage, and enhances adhesion to a light-transmissive film; a hard coat film using the same; and a laminate thereof.SOLUTION: An active energy ray-curable composition for forming a hard coat layer comprises: an active energy ray-curable component (A) comprising a multifunctional urethane (meth)acrylate (a1) having 6 or more (meth)acryloyl groups and a norbornane ring skeleton; an ultraviolet shielding agent (B); a photopolymerization initiator (C); a color adjustment agent (D); and a solvent (E), wherein the photopolymerization initiator (C) comprises an oxime ester-based derivative.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active energy ray-curable composition for forming a hard coat layer, The present invention relates to a coated film and a laminate thereof.

[0002] More specifically, TVs, laptops, mobile phones, smartphones, e-books and To obtain a hard coat film that can be applied to displays such as signage The active energy ray curable composition for forming a hard coat layer, and the hard coat film using the same The present invention relates to a laminate thereof. [Background technology]

[0003] It has long been used in displays for TVs, notebook computers, mobile phones, smartphones, etc. In addition to the liquid crystal display (LCD) that was used, various other displays were developed, Products that take advantage of these features are being introduced to the market.

[0004] Organic electroluminescence (EL) displays are one of them, and are used in TVs and smartphones. It is rapidly expanding into various applications such as smartphones.

[0005] LCD displays and OLED displays are best suited for video playback, but still image playback It has the characteristics of high response speed, high visibility, and the ability to retain displayed information even when the power is off or at very low power consumption. In recent years, electronic paper has become more and more colored, and is being used for applications such as electronic books and electronic signage. Development and commercialization is progressing toward this goal.

[0006] For display products, the adverse effects of external ultraviolet rays on display functions are an issue. This is particularly serious in outdoor applications. To prevent the effects of external ultraviolet rays, a UV-cut layer is placed on the outside of the functional layer to be protected. It is common to set up In addition, by providing an ultraviolet ray blocking layer on the outside of the functional layer that needs to be protected, the inside of the display is protected from ultraviolet rays. It can also protect your eyes from harmful ultraviolet rays emitted by sunlight.

[0007] Display products, especially notebook computers, mobile phones, smartphones, pads, Mobile devices such as smartwatches and e-books place importance on portability, so they are becoming lighter and smaller. As display sizes continue to shrink, the functional layers in the display configuration are being considered for multi-functioning and thinning. In the study of thinning, the thickness of the base film is being reduced, and thin films of 50 μm or less are being developed. Other measures are also being considered. When an active energy ray curing material is applied to a film, it generally causes warping due to curing shrinkage, Curling often occurs, and this tendency becomes more pronounced as the film base becomes thinner. Since displays are constructed by laminating functional layers, the curl of the substrate after the formation of the functional layers occurs later. This leads to deterioration of workability in the process and a decrease in yield.

[0008] Patent Document 1 describes a UV-absorbing material that has both hard coat properties and UV-absorbing properties. A hard coat film is exemplified.

[0009] However, if the transmittance (T)% at 380 nm is not set to an appropriate value, the UV rays will not be absorbed sufficiently. It is not possible to cut the light to a level that would adversely affect display products. When the transmittance (T)% of the When using triazine-based UV cut agents, transmittance decreases around 420 nm. In addition, in order to make the screen even thinner, the UV protection agent is required. The amount of additive will increase, and the yellow color will become stronger. This adversely affects the white clarity of the image.

[0010] In addition, because it uses an initiator that generates radicals when exposed to ultraviolet light, including the visible light region, It has poor storage stability over time, and is easily affected by environmental factors such as lighting and temperature during coating work. However, there are still issues in terms of yield.

[0011] In Patent Document 2, a resin layer containing a specific ultraviolet ray blocking agent is provided on a base film. A surface protection film that is less colored and has excellent scratch resistance is given as an example.

[0012] However, the UV-cutting agent is a benzotriazole-based compound and a triazine-based compound. As long as the compound is selected, the problem of yellowing due to the decrease in transmittance from around 420 nm and the thinness When trying to make the product more flexible, the problem of increased yellowing due to the increased amount of additive occurs, just like in Patent Document 1. , adversely affecting the white clarity of the display product.

[0013] In addition, Patent Document 2 describes a UV initiator that has absorption up to about 390 nm. Since the absorption wavelength edge of the UV-blocking agent and the cut wavelength region of the UV-blocking agent are the same or close to each other, sufficient UV If the curing property is not obtained, adhesion decreases, and physical properties such as coating hardness decrease, resulting in defects. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] JP 2009-6513 A [Patent Document 2] JP 2016-107498 A Summary of the Invention [Problem to be solved by the invention]

[0015] The present invention protects the display part from ultraviolet rays from the outside and improves the white color clarity. Prevents scratches during the production process, prevents curling due to hardening shrinkage, and prevents light transmission from occurring Active energy ray curable composition for forming a hard coat layer with improved adhesion, and The object of the present invention is to provide a hard coat film and a laminate thereof. [Means for solving the problem]

[0016] As a result of extensive research into the above-mentioned problems, the present invention provides an active energy ray-curable film as described below. They found that this problem could be solved by using a chemically resistant composition, and thus completed the present invention.

[0017] The present invention relates to a composition for forming a hard coat layer on a light-transmitting film, comprising: Energy ray curing component (A), UV cut agent (B), photopolymerization initiator (C), color tone The active energy ray curable component (A) comprises a stabilizer (D) and a solvent (E), ) A polyfunctional urethane (meth) having six or more acryloyl groups and a nurate ring skeleton. The photopolymerization initiator (C) contains an oxime ester derivative. The present invention relates to an active energy ray-curable composition for forming a hard coat layer.

[0018] The present invention also provides a method for producing the active energy ray curable component (A) comprising the step of: A polyfunctional compound having 4 to 15 alkyl groups and a weight average molecular weight of 500 to 15,000. Urethane (meth)acrylates (excluding (a1)) (a2) and other multifunctional ( The active energy ray curable composition for forming a hard coat layer, which contains (a3) ​​meth)acrylate. Related to the composition.

[0019] Further, the present invention provides a method for forming a hard coat layer by applying the active energy ray for forming a hard coat layer to a light-transmitting film. The present invention relates to a hard coat film having a hard coat layer formed by curing a curable composition.

[0020] In addition, the present invention provides a method for manufacturing a reflective optical fiber having a transmittance (ta) of 3% or less at a wavelength of 380 nm and a transmittance (ta) of 3% or less at a wavelength of 420 nm. The hard coat film has a transmittance (tb) at m of 65% or more.

[0021] The present invention also provides L * a * b * In the color system, b * is between -1.5 and 3.0 The present invention relates to the hard coat film.

[0022] The present invention also provides L * a * b * In a * is greater than or equal to -2.5 and less than or equal to 1.5 Regarding hard coat films.

[0023] The present invention also provides an optical laminate comprising the hard coat film and other functional layers. Related to body electronic devices. Effect of the Invention

[0024] This invention protects the display from external ultraviolet rays and improves the clarity of white light. This prevents scratches during the production process, prevents curling due to hardening shrinkage, and provides light transmission. and an active energy ray curable composition for forming a hard coat layer which improves adhesion to a substrate. It is possible to provide a hard coat film and a laminate thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will be described in detail below. However, other embodiments may be used as long as they are consistent with the spirit of the present invention. It goes without saying that the present invention also includes the above-mentioned forms. The numerical range specified using "~" is the range between the lower and upper limits. This includes the above as an enclosure.

[0026] First, the terms used in this specification will be explained. As used herein, the terms "(meth)acrylic", "(meth)acryloyl", and "(meth) When "acrylate" is written, it means "acrylic or "Methacryloyl," "Acryloyl or Methacryloyl," and "Acrylate or Methacryloyl" "Acrylate" is intended to represent In addition, the "active energy ray curable composition for forming a hard coat layer" is "(Meth)acryloyl group having 6 or more and nurate ring skeleton" "Urethane (meth)acrylate (a1)" to "Urethane (meth)acrylate (a1)" "Having 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 500 or more." Polyfunctional urethane (meth)acrylates having a molecular weight of 15,000 or less (excluding (a1)) a2)" should be described as "polyfunctional urethane (meth)acrylate (a2)" Unless otherwise noted, each of the various components appearing in this specification represents one type independently. Alternatively, two or more of them may be used in combination.

[0027] <Active energy ray-curable component (A)> The active energy ray-curable component (A) has six or more (meth)acryloyl groups and is The polyfunctional urethane (meth)acrylate (a1) has a acrylate ring skeleton. p) having 4 to 15 acryloyl groups and a weight average molecular weight of 500 to 15,000; 00 (excluding (a1)) (a2), and It is preferable that the polyfunctional (meth)acrylate (a3) ​​is contained. A multifunctional urethane (meth)acrylate is a compound having a urethane bond and a (meth)acrylate bond. It refers to an oligomer having two or more amide groups.

[0028] <Polyfunctional urethane (meth)acrylate (a1)> The urethane (meth)acrylate (a1) has six or more (meth)acryloyl groups, The nurate ring skeleton is an isocyanate compound having a nitrogen atom. It is a trimer of the compound and has a six-membered ring structure. By having six or more (meth)acryloyl groups, The crosslink density is increased, the hardness and scratch resistance of the hard coat film surface are excellent, and the hard coat film The detailed factors that suppress curling are unknown, but the nurate ring It is believed that the ring structure of the skeleton contributes greatly to stress relaxation. Compounds with three (meth)acryloyl groups and a nurate ring skeleton are also relatively easy to obtain. However, due to the low crosslink density, the hardness and scratch resistance of the hard coat film surface are insufficient, making it unsuitable. .

[0029] As the urethane (meth)acrylate (a1), specifically, isopropyl alcohol of diisocyanate A reaction product of cyanurate (trimer) and a poly(meth)acrylate compound having a hydroxyl group, Polyisocyanate isocyanurate (trimer) and polyol and polyol with hydroxyl groups. Examples of the reaction products include those with acrylate or mono(meth)acrylate compounds. From the viewpoint of excellent surface hardness and scratch resistance, isocyanurate (trimer) of diisocyanate ) compound and a poly(meth)acryloyl group having one hydroxyl group and two or more (meth)acryloyl groups. Reaction products with acrylate compounds are preferred.

[0030] Diisocyanates include tolylene diisocyanate and xylylene diisocyanate. and aromatic diisocyanates such as diphenylmethane diisocyanate, Hydrogenated isocyanates, as well as isophorone diisocyanate, hexamethylene diisocyanate, Examples of the isocyanate include aliphatic diisocyanurates such as isocyanates. Mono(meth)acrylates having one hydroxyl group include 2-hydroxyethyl(meth)acrylates. Acrylates, 2-hydroxypropyl (meth)acrylate, and 4-hydroxypropyl (meth)acrylate butyl (meth)acrylate, etc., and poly(meth)acrylate having one hydroxyl group. Examples of the acrylate include pentaerythritol tri(meth)acrylate and dipentaerythritol. Examples of the acrylate copolymer include, but are not limited to, thol penta(meth)acrylate.

[0031] The polyol may be ethylene glycol, polyethylene glycol, polypropylene glycol, Polyethylene glycol, glycerin, trimethylolpropane, cyclohexanediol, cyclohexanediol Examples include cyclohexanedimethanol and tricyclodecane dimethanol. However, the present invention is not limited to the above.

[0032] Polyfunctional urethane (meth)acrylate in 100% by mass of active energy ray curable component (A) The content of the acetate (a1) is preferably from 12 to 48 mass %. By adjusting the thickness within this range, curling can be suppressed.

[0033] <Polyfunctional urethane (meth)acrylate (a2)> The polyfunctional urethane (meth)acrylate (a2) has 4 or more (meth)acryloyl groups. A polyfunctional urethane (meth)acrylate having 15 or less units and a weight average molecular weight of 500 to 15,000. (a) Acrylate (excluding (a1)). The weight average molecular weight is the hardness of the coating film after curing. In order to improve the viscosity and maintain good curling properties, the molecular weight is preferably 1,000 to 5,000. The average molecular weight (Mw) was determined by gel permeation chromatography (GPC). The weight average molecular weight is calculated based on polystyrene. The weight average molecular weight is shown in the [Examples] section. It can be measured by the method described.

[0034] The polyfunctional urethane (meth)acrylate (a2) is a urethane (meth)acrylate (a By using it in combination with 1), the crosslink density, flexibility, and adhesion to the substrate are well balanced, and the resistance to scratches and cracks is reduced. This can reduce the occurrence of warping.

[0035] The polyfunctional urethane (meth)acrylate (a2) can be, for example, a polyisocyanate and a hydroxyl group. and a mono(meth)acrylate or poly(meth)acrylate having a group. Polyol and polyisocyanate are reacted under the condition of excess isocyanate group. The resulting isocyanate group-containing urethane prepolymer is mixed with a mono(meth)acrylate having a hydroxyl group. and those obtained by reacting with acrylate or poly(meth)acrylate. Alternatively, a hydrophilic polyisocyanate is prepared by reacting a polyol with a polyisocyanate under conditions of excess hydroxyl groups. The acid group-containing urethane prepolymer is mixed with (meth)acrylates having an isocyanate group. It can also be obtained by reaction.

[0036] The method for producing the urethane (meth)acrylate (a2) is shown below as an example. For example, the urethane (meth)acrylate (a2) is a polyimide. A socyanate and a hydroxyl group-containing (meth)acrylate are reacted in the presence of a suitable urethane catalyst. The mixture can be obtained by stirring in an oxygen atmosphere at 60 to 100° C. for 4 to 8 hours. Specific examples of the urethane catalyst include copper naphthenate, cobalt naphthenate, and zinc naphthenate. Lead, dibutyltin dilaurate, triethylamine, 1,4-diazabicyclo[2.2. 2]octane, 2,6,7-trimethyl-1,4-diazabicyclo[2.2.2]octa Among these, dibutyltin dilaurate is particularly preferred. .

[0037] The polyisocyanate may be, for example, an aliphatic diisocyanate, an aromatic diisocyanate, etc. Examples of aliphatic diisocyanates include hexamethylene diisocyanate and isophorone. Long diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated diphenyl meth Examples of aromatic diisocyanates include toluene diisocyanate. diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, etc. The bonding position of the isocyanate group to the aromatic group can be any of the ortho, meta, and para positions. The diisocyanate may also form an isocyanurate ring as a trimer. . Among these, aliphatic diisocyanates are preferred from the viewpoint of suppressing yellowing when optical applications are envisaged. It is nice.

[0038] The (meth)acryloyl number and the weight average molecular weight are determined by the polyol, polyisocyanate, and hydroxyl. Adjust by combining group-containing mono(meth)acrylates or poly(meth)acrylates. It is possible.

[0039] Hydroxyl-containing (meth)acrylates include trimethylolpropane di(meth)acrylate. acrylate, trimethylolethane di(meth)acrylate, pentaerythritol tri( (meth)acrylate, dipentaerythritol penta(meth)acrylate, (meth)a 2-Hydroxyethyl acrylate, 1-hydroxypropyl (meth)acrylate, (meth) 2-Hydroxypropyl acrylate, 3-hydroxypropyl (meth)acrylate, (meth)acrylate 1-hydroxybutyl, (meth)acrylate 2-hydroxybutyl, (meth)acrylate 3-Hydroxybutyl (meth)acrylate, 4-Hydroxybutyl (meth)acrylate, 6-Hydroxyhexyl (meth)acrylate, 8-Hydroxyoctyl (meth)acrylate , Cyclohexanedimethanol mono(meth)acrylate, (meth)acrylic acid 1 0-Hydroxydecyl, (meth)acrylate 12-Hydroxylauryl, (meth)acrylate ethyl acrylate-α-(hydroxymethyl), monofunctional (meth)acrylate, Alternatively, these (meth)acrylates and ε-caprolactone lactone can be added to form terminal esters. (Meth)acrylic acid esters having a hydroxyl group at the end and the above-mentioned hydroxyl group-containing (meth)acrylates Alkaline oxides such as ethylene oxide, propylene oxide, and butylene oxide are used against Repeated addition of alkylene oxide to (meth)acrylic acid ester Examples of suitable acrylates include hydroxyl group-containing (meth)acrylic esters such as acrylates. In order to increase the crosslink density and prevent scratches and curling, the (meth)acryloyl group is added to 2 to 100% of the polymer. (Meth)acrylic acid esters having 5 units are preferred. Specifically, trimethylolpropane Trimethylolethane di(meth)acrylate, Pentaerythritol di(meth)acrylate Thuritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate It is preferable that the polyolefin resin contains at least one selected from the group consisting of olefins, olefins having a molecular weight of 1,000 to 1,000.

[0040] Urethane acrylates whose molecular weight and number of acryloyl groups are published in catalogs, etc. a2) Mitsubishi Chemical Corporation's UV1700B (molecular weight 2000, acrylic) 10 acryloyl groups), UV7600B (molecular weight 1400, 6 acryloyl groups), UV76 05B (molecular weight 1100, acryloyl group number 6), UV7610B (molecular weight 1100, acryloyl group number 6) Acryloyl group number 9), UV7629EA (molecular weight 4100, acryloyl group number 9, volatile content 35%), UV7640B (molecular weight 1500, number of acryloyl groups 6-7), and UV7 Mira 650B (molecular weight 2300, 4-5 acryloyl groups), manufactured by MIWON Co., Ltd. merPU610 (molecular weight 1800, 6 acryloyl groups) and MU9500 (molecular weight Amount 3200, number of acryloyl groups 10), Nippon Kayaku Co., Ltd.: KAYARAD DPHA 40H (molecular weight 2000, 10 acryloyl groups), UX-5000 (molecular weight 1500, UX-5102D-M20 (molecular weight 3500, acryloyl group number 6) Volatile content 20%), UX-5103 (molecular weight 7000, number of acryloyl groups 6), and UX -5005 (molecular weight 4500, acryloyl group number 9), manufactured by Negami Chemical Industries, Ltd.: Art Resin UN-3320HA (molecular weight 1500, acryloyl group number 6), UN-3320HC (molecular weight Molecular weight 1500, acryloyl group number 15, volatile content 5%), UN-904 (molecular weight 4900, Acryloyl group number 10), UN-906S (molecular weight 1000, acryloyl group number 6), U N-901T (molecular weight 4000, acryloyl group number 9, volatile content 20%), and UN-9 52 (molecular weight 6500-11000, 10 acryloyl groups) and the like. Not limited.

[0041] Polyfunctional urethane (meth)acrylate in 100% by mass of active energy ray curable component (A) The content of the acetate (a2) is preferably from 20 to 80 mass %. By adjusting the thickness within this range, high scratch prevention can be achieved.

[0042] <Other polyfunctional (meth)acrylates (a3)> The other multifunctional (meth)acrylate (a3) ​​is a multifunctional (meth)acrylate other than (a1) and (a2). It is a functional (meth)acrylate. Other polyfunctional (meth)acrylates (a3) ​​include various diol (meth)acrylates. acrylate, trimethylolethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate Pentaerythritol tri(meth)acrylate, Pentaerythritol Dipentaerythritol tetra(meth)acrylate, Dipentaerythritol penta(meth)acrylate , dipentaerythritol hexa(meth)acrylate, and various other polyols (poly(meth)acrylates) Acrylates, tri(meth)acrylates of isocyanurates of various diisocyanates , other than the polyfunctional urethane acrylate (a1) and the polyfunctional urethane acrylate (a2) Examples of the urethane acrylate include, but are not limited to, the following. Urethane (meth)acrylate (a1) and urethane (meth)acrylate (a2) Pentaerythritol triacrylate (a3-1), pentaerythritol, remaining during synthesis Dipentaerythritol tetraacrylate (a3-2), Dipentaerythritol pentaacrylate ( a3-3), and dipentaerythritol hexaacrylate (a3-4) as is Can be used.

[0043] Other examples of the polyfunctional (meth)acrylate (a3) ​​include those having 2 to 4 (meth)acryloyl groups. A multifunctional acrylate having 5 nurate rings and a nurate ring skeleton, manufactured by Toagosei Co., Ltd. Isocyanuric acid EO modified diacrylate (acryloyl group number 2) such as Nix M-215 , Toagosei Co., Ltd.: Aronix M-313, and Toagosei Co., Ltd.: Aronix M- EO-modified diacrylate and / or triacrylate (acrylic acid) such as 315 ε-ester A-9300-1CL, etc., manufactured by Shin-Nakamura Chemical Co., Ltd. Caprolactone-modified (2-acryloxy) isocyanurate (acryloyl group number 3), In addition, Shin-Nakamura Chemical Co., Ltd.: NK Ester A-9300, Arkema Co., Ltd.: SARTO MER SR368, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.: NEW FRONTIER TEICA (G X-8430), and Showa Denko's FANCRYL FA-731A and other tris(2- acryloxyethyl) isocyanurate (acryloyl group number 3), etc. Not limited to.

[0044] In addition, other polyfunctional (meth)acrylates (a3) ​​include those having a (meth)acryloyl group. The number of molecules is outside the range of 4 to 15, or the weight average molecular weight is outside the range of 500 to 15,000. It is a multifunctional urethane acrylate. Mitsubishi Chemical Corporation: Shiko UV-6300B (molecular weight 3700, number of acryloyl groups 3) , Negami Chemical Industries Co., Ltd.: Art Resin UN-5500 (molecular weight 50,000, acryloyl group) 12.5, volatile content 50%), UN-5507 (molecular weight 17000, number of acryloyl groups 1 5.5, volatile content 50%), and UN-905 (molecular weight 40,000 to 200,000, acrylic acid (Number of aryl groups: 15, Volatile content: 40%), and MiramerS manufactured by MIWON Co., Ltd. Examples include urethane acrylates such as C2152 (molecular weight 20787, number of acryloyl groups 15). These include, but are not limited to:

[0045] Other polyfunctional (meth)acrylates in 100% by mass of active energy ray-curable component (A) The content of the compound (a3) ​​is preferably 8 to 32 mass %. By adjusting the content within this range, Adhesion can be achieved.

[0046] Multifunctional urethane (meth)acrylate contained in active energy ray-curable component (A) The mass ratio (a1) / (a2) of (a1) to the polyfunctional urethane (meth)acrylate (a2) is , 20 / 80 to 80 / 20 is preferable, and 60 / 40 to 40 / 60 is more preferable. By setting (a1) / (a2) at 20 / 80~80 / 20, scratches during the process and the base material can be prevented. It is possible to improve adhesion to the material and suppress curling.

[0047] <UV protection agent (B)> The ultraviolet ray blocking agent (B) refers to an ultraviolet ray absorbing agent. The composition for forming a hard coat layer has ultraviolet absorbing properties. As an ultraviolet ray blocking agent (B), it is recommended to add a small amount of ultraviolet ray absorbing agent in order to prevent bleeding and to reduce costs. Those with excellent yield are preferred. Examples of such ultraviolet ray blocking agents include benzotriazoles, hydroxyphenyls, Examples of such ultraviolet ray blocking agents include triazine-based and benzophenone-based ultraviolet ray blocking agents. Hydroxyphenyl ether is preferred in terms of minimizing the adverse effects on other physical properties of the coating. The ultraviolet ray blocking agent is preferably a triazine type or a benzotriazole type. A commercially available product may be used as it is, or two or more types of commercially available products may be mixed and used.

[0048] Examples of commercially available UV-blocking agents include those sold by Ciba Specialty Chemicals Co., Ltd. "TINUVIN" series (benzotriazole and hydroxyphenyl) manufactured by "U" series manufactured by BASF Ltd. VINUL series (benzophenone and triazine), a product of Otsuka Chemical Co., Ltd. Product name: "RUVA" series (benzotriazole type), product name of ADEKA Corporation Adegastab LA series (benzotriazole and triazine), Ever "Eversorb" series (benzodiazepines) manufactured by Light Chemicals triazole-based, triazine-based, benzophenone-based) and the like.

[0049] The content of the ultraviolet ray blocking agent (B) is 100% by mass of the active energy ray curable component (A). For example, it is in the range of 0.5 to 20 mass %, and preferably in the range of 2 to 15 mass %. By setting the content at 0.5 to 20 mass%, it is possible to sufficiently block ultraviolet rays while photoexciting the photopolymerization initiator. This ensures that the ultraviolet rays necessary for curing can be obtained, thereby improving the curing properties of the coating film.

[0050] <Photopolymerization initiator (C)> The photopolymerization initiator (C) includes an oxime ester derivative. The active energy ray-curable composition of the present invention contains an ultraviolet ray blocking agent, which has no effect on the laminate. In order to block ultraviolet rays with wavelengths of approximately 400 nm or less, which are close to visible light that has a negative effect on the eyes, UV lamps containing mercury, such as high pressure mercury lamps and metal halide lamps used for radiation curing Many photopolymerization initiators emit light with wavelengths of 313 nm (j-line) and 365 nm (i-line). The ultraviolet light required for excitation is also blocked. However, the use of oxime ester derivatives It emits radiation by photoexcitation using ultraviolet light of 400 nm or more (for example, H-rays at 405 nm). The polymerization can be initiated.

[0051] As a conventionally known oxime ester derivative, there is Irgacu manufactured by BASF Ltd. re OXE01, Irgacure OXE02, Irgacure OXE03, Ir gacure OXE04, etc., Nikkacure YJ-04 manufactured by Nippon Chemical Industry Co., Ltd. , IW-15, etc., and ADEKA Arcles NCI-831E manufactured by ADEKA Corporation. .

[0052] The photopolymerization initiator (C) is used in combination with other photopolymerization initiators other than oxime ester derivatives. Other examples of the photopolymerization initiator include acetophenone compounds and benzoin compounds. compounds, benzophenone compounds, phosphine oxide compounds, ketal compounds, anthraquinone compounds Examples of the compounds include benzoin methyl ether, benzoyl ... Benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether ether, diethoxyacetophenone, benzyl dimethyl ketal, 1-hydroxycyclohexyl Hexyl phenyl ketone, benzophenone, 2,4,6-trimethylbenzoin diphenyl Phosphine oxide, N,N-dimethylaminobenzoic acid isoamyl, 2-chlorothioxanthate Examples include xanthone and 2,4-diethylthioxanthone.

[0053] The initiator used in combination must be as small as possible and must generate radicals efficiently even with slight ultraviolet light. A highly sensitive initiator capable of reacting with the amine is preferred. Specifically, 4,4'-bis(dimethylamine) Benzophenone, 4,4'-bis(diethylamino)benzophenone and other dialkyl Aminobenzophenone derivatives, camphorquinone derivatives such as (±)-camphorquinone, S Herwin-Williams Ultracure CTX, Ultra cu re DTX, Ward-Blenkinsop: Quantacure ITX, Thioxanthone derivatives such as isopropylthioxanthone and 2,4-diethylthioxanthone BASF's TBA, anthraquinone derivatives such as 2-ethylanthraquinone, etc. Some examples include:

[0054] The amount of the photopolymerization initiator (C) to be blended is 100% by mass of the active energy ray-curable component (A). %, the content is preferably 0.1 to 30 mass%, and more preferably 1 to 15 mass%. By providing such a content, a sufficient polymerization initiation effect can be obtained, which is effective in improving adhesion and scratch resistance.

[0055] <Color tone adjuster (D)> The color tone adjusting agent in the present invention is an additive that adjusts the color tone by absorbing light in the visible light region. The type of the color tone adjusting agent is not particularly limited, but in order to adjust the yellowness of the hard coat layer, As a colorant that exhibits blue or purple, known dyes or pigments can be used.

[0056] In addition, the blue color adjuster used to adjust the yellow color gives the product a greenish color (a * But-( If the color shifts to the inactive side, add a color adjuster that changes color to red or purple. * a * b * By adjusting the coordinates to the center of the color system, * Compared to color adjustment by adjusting the This can improve white clarity. Known dyes and pigments can be used as color tone adjusters that provide red or purple color.

[0057] As for dyes, organic dyes include monoazo dyes that have an azo group in the molecule, triaryl dyes, etc. Methane dyes, phthalocyanine dyes, anthraquinone dyes, and other inorganic dyes. Long Blue, Prussian Blue, Berlin Blue, Turnbull Blue, Milory Blue, Chinese Blue, Paris Blue, and other Prussian Blues (iron cyano complex colorants); Ultramarine Examples of blue include ultramarine blue, cone blue, ultramarine violet, and cobalt blue. As the pigment, for example, CI Pigment Blue 15, 15: 1, 15:2, 15:3, 15:4, 15:6, 16, 22, 60, 80, etc. Among them, the blue complexion selected from the group consisting of CI Pigment Blue 15:6 It is preferable to use a As a purple pigment, CI Pigment Violet 19 or CI Pigment ent Violet 23 is preferred. Red pigments include, for example, CI Pigment Red 7, 9, 14, 41, 4 8:2, 48:3, 48:4, 81:1, 81:2, 81:3, 97, 122, 123, 146, 149, 168, 178, 180, 184, 185, 187, 192, 200, 202, 208, 210, 215, 216, 217, 220, 223, 224, 226, Examples include 227, 228, 240, 246, 255, 264, and 272. Among them, CI Pigment Red 48: 1, 177, 242 and 254 It is preferable to use a red pigment that is suitable for this purpose.

[0058] From the viewpoints of heat resistance, light resistance, and weather resistance, it is preferable to use pigments. It provides heat resistance, light resistance, and weather resistance that makes it suitable for various applications. The color tone adjusting agents can be used alone or in combination of two or more.

[0059] The content of the color tone adjusting agent is determined so that the hard coat film having a hard coat layer of a predetermined thickness is The transmittance can be adjusted appropriately to obtain a desired transmittance. The transmittance (ta) of the hard coat film having a reflective layer at 380 nm is 3% or less. In this case, in order to suppress yellowing and to improve transparency, 100 mass % of the active energy ray-curable component (A) is used. %, the content of the color tone adjusting agent is preferably 0.001 to 4.0 mass%, and 0. 0.1 to 2.5 mass % is more preferable.

[0060] When using a pigment as a color tone adjuster, the pigment should be adjusted in size in order to prevent the hard coat layer from being too transparent. The volume average primary particle diameter is preferably 150 nm or less, and the average of the pigment in the composition The dispersed particle size (D50) is preferably 10 to 150 nm.

[0061] The volume average primary particle diameter of the pigment was measured using a transmission electron microscope (TEM) photograph of 100 particles. The minor and major axis diameters of the primary pigment particles are measured, and the average of the minor and major axis diameters is calculated as the particle diameter of the pigment particles. (d) Then, assuming that each pigment is a sphere having the desired particle size, the volume of each particle is calculated. The product (V) is calculated and this operation is carried out for 100 pigment particles, and the product is obtained from the following formula: The volume average particle size (MV) is taken as the average primary particle size. MV = Σ(V d) / Σ(V) The average dispersed particle diameter (D50) of the pigment in the composition is measured using a particle size distribution measuring device, especially a dynamic A particle size distribution measuring device using light scattering (Microtrack Bell's "NANOTRAC This can be measured using a meter such as the WAVE II EX150.

[0062] To obtain pigments with a volume average primary particle size of 150 nm or less, for example, salt milling is required. It is possible to achieve extremely fine grained structures. In addition, the average dispersed particle diameter (D5 In order to obtain 0), it is preferable to disperse the pigment. It is preferred to use a pigment dispersion.

[0063] The pigment dispersion obtained by dispersing the pigment is a mixture of a pigment, a dispersant, and / or a binder resin, an organic The mixture containing the solvent is mixed in a kneader, a two-roll mill, a three-roll mill, a ball mill, or a horizontal mill. Sand mill, vertical sand mill, annular bead mill, or attritor It can be produced by finely dispersing it using a dispersion means (pigment dispersion). It is preferable to disperse beads using inorganic glass or inorganic glass. May be used.

[0064] When dispersing pigments, dispersants such as dye derivatives, resin-type dispersants, and surfactants are appropriately added. Fine pigments tend to reaggregate and may reduce the transparency of the coating film, but dispersants Since it has a great effect of preventing reagglomeration of the pigment, the transparency of the coating film becomes good.

[0065] The dye derivatives include those having a basic or acidic substituent in the dye skeleton. For example, JP 63-305173, JP 57-15620, JP 59-401 72, JP-B-63-17102, or JP-B-5-9469. These may be used alone or in combination of two or more. .

[0066] Resin-type pigment dispersants consist of a pigment affinity site that has the property of adsorbing to the pigment and a pigment carrier. and a site compatible with the pigment, and functions to adsorb to the pigment and stabilize the dispersion of the pigment in the dye carrier. Specifically, polyurethane, polyacrylate, etc. are used as resin-type pigment dispersants. Polycarboxylic acid esters such as ethyl esters, unsaturated polyamides, polycarboxylic acids, polycarboxylic acids (Partial) amine salts, ammonium polycarboxylates, alkylamine polycarboxylates, Polysiloxane, long-chain polyaminoamide phosphate, hydroxyl-containing polycarboxylate and their modified products, poly(lower alkyleneimine) and poly(lower alkyleneimine) having a free carboxyl group. Oil-based dispersants such as amides and their salts formed by reaction with (meth)acrylic acid esters. acrylic acid-styrene copolymer, (meth)acrylic acid-meth)acrylic acid ester copolymer, Styrene-maleic acid copolymer, polyvinyl alcohol, polyvinylpyrrolidone, etc. Water-soluble resins, water-soluble polymer compounds, polyesters, modified polyacrylates, ethylene oxides oxide / propylene oxide adducts, phosphate esters, etc. are used. They can be used alone or in combination of two or more.

[0067] A commercially available resin-type dispersant is DISPERBYK-1 manufactured by BYK Japan. 01, 103, 107, 108, 109, 110, 111, 116, 130, 140, 1 54,161,162,163,164,165,166,167,168,170,1 71, 174, 180, 181, 182, 183, 184, 185, 190, 2000, 2001, 2020, 2025, 2050, 2070, 2095, 2150, 2155, 2163, 2164, or Anti-Terra-U, 203, 204 or BYK- P104, P104S, 220S, 6919, or Lactimon, Lactimo SOLSPERSE-30 made by Louvre Resol Japan, such as n-WS or Bykumen 00, 9000, 11200, 13000, 13240, 13650, 13940, 16 000, 17000, 18000, 20000, 21000, 24000, 26000, 27000, 28000, 31845, 32000, 32500, 32550, 3300 0, 33500, 32600, 34750, 35100, 35200, 36600, 37 500, 38500, 39000, 41000, 41090, 53090, 56000, 55000, 71000, 76500, etc., BASF EFKA-46, 47, 48, 452, 4008, 4009, 4010, 4015, 4020, 4047, 4050, 4 055, 4060, 4080, 4400, 4401, 4402, 4403, 4406, 4 408, 4300, 4310, 4320, 4330, 4340, 4500, 4510, 4 530, 4540, 4550, 4560, 4800, 5010, 5065, 5066, 5 070, 7500, 7554, 1101, 120, 150, 1501, 1502, 150 3rd place: Ajinomoto Fine-Techno Co., Ltd.'s Ajisper PA111, PB711, PB821, P B822, PB824, etc.

[0068] Surfactants include polyoxyethylene alkyl ether sulfate and dodecylbenzene. Sodium sulfonate, alkali salt of styrene-acrylic acid copolymer, alkyl naphtha Sodium phosphorus sulfonate, sodium alkyl diphenyl ether disulfonate, lauryl sulfate Monoethanolamine lauryl sulfate, Triethanolamine lauryl sulfate, Aminoethanolamine lauryl sulfate Mononium, Monoethanolamine Stearate, Sodium Stearate, Lauryl Sulfate Sodium, styrene-acrylic acid copolymer monoethanolamine, polyoxyethylene Anionic surfactants such as olefin alkyl ether phosphate esters; Polyoxyethylene nonyl ether, polyoxyethylene lauryl ether, polyoxyethylene nonyl Phenyl ether, polyoxyethylene alkyl ether phosphate ester, polyoxyethylene Noni such as polyethylene sorbitan monostearate and polyethylene glycol monolaurate Ionic surfactants; alkyl quaternary ammonium salts and their ethylene oxide adducts Cationic surfactants such as alkyl dimethylaminoacetate betaine; Amphoteric surfactants such as tine and alkyl imidazoline are also included. These may be used alone or Two or more types can be mixed and used.

[0069] When a dispersant is added, the amount is preferably 0.1 to 200 parts by mass per 100 parts by mass of the pigment. and more preferably 0.1 to 150 parts by mass. If the amount of the dispersant is less than 0.1 parts by mass, it is difficult to obtain the desired effect. If the amount is more than 200 parts by mass, the excess dispersant may adversely affect dispersion.

[0070] The binder resin is capable of forming a thin film layer and dispersing the pigment. As the binder resin, for example, a known thermoplastic resin can be used. Examples include energy ray curable resins such as resins, UV curable resins, and heat curable resins. Examples of the curable resin include resins having a polymerizable functional group such as a (meth)acryloyl group. These resin components may be used alone or in combination of two or more. Among these, the resin component is effective in increasing the curing property of the final composition coating film, and in improving the hardness and density of the coating film. Energy ray curable resins such as UV curable resins are preferred because they improve physical properties such as adhesion.

[0071] <Solvent (E)> Solvents (E) include dimethyl carbonate, ethyl acetate, n-butyl acetate, acetone, and methyl Ethyl ketone, cyclohexanone, 1,3-dioxolane, methyl isobutyl ketone, isopropyl alcohol, Propyl alcohol, propylene glycol monomethyl ether, propylene glycol Examples of the ethyl alcohol include, but are not limited to, ethyl acetate, toluene, etc. They can be used alone or in combination of two or more.

[0072] The solvent (E) is, in 100 mass % of the active energy ray-curable composition for forming a hard coat layer, It is preferably 40 to 80 mass%, more preferably 40 to 70 mass%, The content is more preferably 45 to 65% by mass. When the content is within the above range, the hard coat layer-forming active energy ray-curable composition has a low Viscosity, coatability, and drying properties can be adjusted.

[0073] <<Active energy ray-curable composition for forming hard coat layer>> The active energy ray-curable composition for forming a hard coat layer of the present invention is Chemical component (A), UV cutter (B), photopolymerization initiator (C), color adjuster (D), and Contains a solvent (E).

[0074] The composition for forming a hard coat layer in the present invention may contain other additives as necessary. Other additives include, for example, plasticizers, surface conditioners, light stabilizers, antioxidants, Polymerization inhibitors are included.

[0075] <Hard coat film> The hard coat film of the present invention is a composition for forming a hard coat layer on a light-transmitting film. The hard coat layer is formed by curing the composition. The hard coat film of the present invention has a transmittance (ta) of 3% or less at a wavelength of 380 nm. In addition, it is preferable that the transmittance (tb) at a wavelength of 420 nm is 65% or more. The transmittance (ta) at a wavelength of 380 nm is 3% or less, It blocks ultraviolet rays that are harmful to the display underneath, preventing deterioration of the display. It can be stopped. In addition, the transmittance (tb) at a wavelength of 420 nm is 65% or more, This makes it possible to improve the clarity of the white color of the play display area. The transmittance (ta) is more preferably 1.5% or less, and the transmittance (tb) is preferably 7% or less from the viewpoint of suppressing yellowing. It is more preferable that the content is 0% or more.

[0076] The hard coat film of the present invention is excellent in terms of white clarity of the display area. * a * b * In the color system, b * is preferably -1.5 or more and 3.0 or less. * but It is preferable that the ratio is greater than or equal to -2.5 and less than or equal to 1.5.

[0077] (Light-transmitting film) The light-transmitting film used in the present invention may be any film having an optically transparent grade. There is no particular limit to the thickness of the film, but it is generally set to 10 mm in terms of strength, ease of handling, thinness, etc. In particular, the thickness is preferably 20 to 250 μm.

[0078] Specific examples of light-transmitting films include amorphous polyolefin resin films, polyester films, and the like. Polyethylene terephthalate resin film, acrylic resin film Polycarbonate resin film, polysulfone resin film, alicyclic polyimide Polycycloolefin resin film, Triacetyl cellulose (T AC) films. By using the most suitable film for the display structure, There are no limitations as long as the material is optically transparent.

[0079] (Hard coat film manufacturing) The method for producing a hard coat film comprises applying a composition for forming a hard coat layer on a light-transmitting film. The method for producing the adhesive layer is not particularly limited, and the adhesive layer can be produced by a conventionally known method, such as coating an object. For example, after the composition for forming a hard coat layer of the present invention is applied to a light-transmitting film, The solvent is then dried according to the temperature. Then, the coated hard coat is irradiated with active energy rays. The composition for forming the light-transmitting film is crosslinked and cured. Thus, a hard coat film having a hard coat layer and a hard coat film having a hard coat layer can be obtained.

[0080] Coating methods include bar coating, blade coating, spin coating, Reverse coating, die coating, spray coating, roll coating, Rabbit coating, microgravure coating, lip coating, air nylon Coating, dipping and the like can be mentioned.

[0081] Examples of active energy rays include electron beams, xenon lamps, low-pressure mercury lamps, high-pressure mercury lamps, and ultra- Light sources such as high pressure mercury lamps, metal halide lamps, carbon arc lamps, and tungsten lamps Ultraviolet light emitted from a light source can be used. By including an ultraviolet ray blocking agent, the active energy ray-curable composition of the present invention can be made to have an ultraviolet ray-absorbing property close to that of visible light. In order to cut ultraviolet rays with a wavelength of around 400 nm, the emission spectrum is set to wavelengths of 400 nm or more. It is preferable to use a high-pressure mercury lamp or a metal halide lamp.

[0082] The thickness of the hard coat layer is not particularly limited as long as it has hard coat properties. 0 μm, and preferably 1 to 15 μm.

[0083] <<Optical laminated electronic device>> The optical laminated electronic device of the present invention is a laminate of a hard coat film and other functional layers. For example, a laminate of a hard coat film and a display function layer can be used. It has a structure of hard coat layer / optical film / display function layer. The method for producing the laminate is not particularly limited. For example, By bonding the light-transmitting film surface, which does not have a light-transmitting layer, to the display functional layer, This allows the formation of a display functional layer laminate that is protected from harmful ultraviolet rays. EXAMPLES

[0084] <Weight average molecular weight (Mw)> The weight average molecular weight was measured using a gel permeation chromatography (HL C-8220GPC" was used, and separation column: Tosoh Corporation's "TSK-GEL SU PER H5000”, “TSK-GEL SUPER H4000”, “TSK-GEL SUPER H3000" and "TSK-GEL SUPER H2000" in a straight line The column was connected, and the mobile phase was tetrahydrofuran at 40°C at a flow rate of 0.6 ml / min. The measured weight average molecular weight is calculated based on polystyrene standards.

[0085] <Average dispersed particle diameter (D50)> The average dispersed particle diameter (D50) was measured using a dynamic light scattering particle size distribution analyzer (Microtrack The measurements were performed using a dilution solvent and a NANOTRAC WAVE II EX150 (manufactured by Epson Corporation). Propylene glycol monomethyl ether acetate was used as the loading index. The average value of three 60-second measurements was used at a concentration where the chromatogram was in the range of 1.0 ± 0.2. Used.

[0086] <Production of polyfunctional urethane acrylate (a1)> (Synthesis Example 1) Urethane acrylate mixed solution (P1): stirrer, reflux condenser, nitrogen inlet tube A four-neck flask equipped with a thermometer and a dropping funnel was filled with Aronix M306 (manufactured by Toagosei Co., Ltd.). Pentaerythritol triacrylate (PE-3A) (a3-1) having a molecular weight of 298 Pentaerythritol tetraacrylate (PE-4A) with 7.5% by weight and molecular weight of 352 (a3-2) 32.5% by mass of pentaerythritol polyacrylate) 5.6 parts by mass and 0.1 parts by mass of Neostan U-810 (manufactured by Nitto Kasei Co., Ltd., tin catalyst) After the liquid temperature reached 50°C, Desmodur Z4470BA (manufactured by Sumika Covestro Co., Ltd.) was added. , non-volatile content 70% by mass (volatile content butyl acetate), isophorone with molecular weight of 667 relative to the non-volatile content Contains 89.9% by mass of isopropyl diisocyanate (IPDI) trimer and has an NCO content of 11.9 1059.3 parts by weight of polyisocyanate solution having nurate rings was added from the dropping funnel to 3 The mixture was added dropwise over 0 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. Fourier transform infrared spectroscopy (FTIR) was then used. After confirming that the peak of the isocyanate group has disappeared in the IR, the temperature is lowered to room temperature. The non-volatile content contained a urethane acrylate having a weight average molecular weight of 1600 and nine acryloyl groups. 75.5% by mass of acrylate (a1-1) and 75.5% by mass of pentaerythritol tetraacrylate ( PE-4A) (a3-2) at 20.8% by mass, and A urethane acrylate resin containing 3.6% by mass of other compounds (f-1) and 86.7% by mass of non-volatile matter. A rate mixture (P1) was obtained.

[0087] (Synthesis Example 2) Urethane acrylate mixed solution (P2): stirrer, reflux condenser, nitrogen inlet tube A 4-neck flask equipped with a thermometer and a dropping funnel was fitted with an Aronix M306 1325.6 mass Add 0.1 parts of Neostan U-810 and 0.1 parts of ethanol. After raising the liquid temperature to 50°C, add Duran TPA-100 (manufactured by Asahi Kasei Corporation, non-volatile content 100% by mass, molecular weight based on non-volatile content) Contains 92.8% by mass of hexamethylene diisocyanate (HDI) trimer of 505, N 545.7 parts by mass of polyisocyanate having a nurate ring with a CO content of 23.1% was dropped. The mixture was added dropwise from the bottom funnel over 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After confirming that the peak of the dimethyl group had disappeared, the temperature was lowered to room temperature, and the weight average A urethane acrylate (a1-2) with 9 acryloyl groups and a molecular weight of 1400 is added to 74. 8% by mass of pentaerythritol tetraacrylate (PE-4A) (a3-2) 0.0 mass%, and 2.2 mass% of other compounds (f-2) not having a (meth)acryloyl group. % by mass, a urethane acrylate mixed liquid (P2) having a non-volatile content of 100% by mass was obtained.

[0088] (Synthesis Example 3) Urethane acrylate mixed solution (P3): stirrer, reflux condenser, nitrogen inlet tube 4-neck flask equipped with a thermometer, dropping funnel, Desmodule Z4470BA 4237 0.3 parts by mass, cyclohexyl dimethanol (molecular weight 144, hydroxyl value 389 mg KOH Add 432.6 parts by weight of 1000g / g of ethanol and 0.1 parts by weight of Neostan U-810 and heat to 80°C. After reacting for 3 hours, the peak intensity of the isocyanate group in FT-IR was reduced to 50% of that before the reaction. After confirming that the reaction had become complete, 4-hydroxybutyl acrylate (molecular weight 144, hydroxyl value 3 89 mgKOH / g) and reacted at 80°C for 3 hours. -After confirming that the isocyanate group peak has disappeared in the IR, cool the temperature to room temperature. In the non-volatile matter, a urethane acrylate having six acryloyl groups with a weight average molecular weight of 4000 was 93.0% by mass of copolymer (a1-3), and other compounds not having a (meth)acryloyl group A urethane acrylate having a non-volatile content of 100.0% by mass, containing 7.0% by mass of compound (f-3). A mixed liquid (P3) was obtained.

[0089] (Synthesis Example 4) Urethane acrylate mixed solution (P4): stirrer, reflux condenser, nitrogen inlet tube In a four-neck flask equipped with a thermometer and a dropping funnel, add Pentaerythritol Tri acrylate (Thermo Fisher Scientific, Pentaacrylate) Lithritol triacrylate (PE-3A), purity 97% or more, molecular weight 298) 894 0.8 parts by mass and 0.1 parts by mass of Neostan U-810 (manufactured by Nitto Kasei Co., Ltd., tin catalyst) After the liquid temperature was increased to 50°C, the liquid was cooled with Desmodur Z4470BA (manufactured by Sumika Covestro Co., Ltd.) Non-volatile content 70% by mass (volatile content butyl acetate), isophorone with molecular weight of 667 relative to non-volatile content Contains 89.9% by mass of diisocyanate (IPDI) trimer and has an NCO content of 11.9%. Polyisocyanate solution having nurate ring (1059.33) was added from the dropping funnel for 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After confirming that the peak of the isocyanate group disappeared by spectroscopy (FT-IR), The temperature was lowered to 300°C, and the non-volatile matter contained 9 acryloyl groups with a weight average molecular weight of 1600. 95.4% by mass of urethane acrylate (a1-1) having a (meth)acryloyl group The non-volatile content of the urea-based polymer is 83.7% by mass, and the non-volatile content of the polymer is 4.6% by mass of other compounds (f-1) that do not have the above-mentioned properties. A tetraacrylate mixed solution (P4) was obtained.

[0090] <Having 4 to 15 (meth)acryloyl groups and a molecular weight of 500 to 1500 0 or less> (Synthesis Example 5) Urethane acrylate mixed solution (Q1): stirrer, reflux condenser, nitrogen inlet tube, In a four-neck flask equipped with a thermometer and a dropping funnel, add Pentaerythritol Tria lylate (Thermo Fisher Scientific, Pentaerythritol Tritol triacrylate (PE-3A), purity 97% or more, molecular weight 298) 533 mass parts, 237 parts by weight of Aronix M306, and 100.1 parts by weight of Neostan U-8. After the liquid temperature reached 50°C, Desmodur I (manufactured by Sumika Covestro, isophorone 224 parts by mass of diisocyanate (IPDI) was added dropwise from the dropping funnel over a period of 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After confirming that the peak of the dimethylformamide group had disappeared, the temperature was lowered to room temperature, and the molecular weight of the non-volatile matter was 90. 0, 82.4% by mass of urethane acrylate (a2-1) having 6 acryloyl groups, Pentaerythritol triacrylate (a3-1) (PE-3A, acryloyl group equivalent 99) at 9.7% by mass, and pentaerythritol tetraacrylate (a3-2) ( A urethane acrylate mixed solution (Q1) containing 7.8 mass % of PE-4A was obtained.

[0091] (Synthesis Example 6) Urethane acrylate mixed solution (Q2): stirrer, reflux condenser, nitrogen inlet tube, A four-neck flask equipped with a thermometer and a dropping funnel was filled with Aronix M403 (manufactured by Toagosei Co., Ltd.). Dipentaerythritol pentaacrylate (DPPA(a3-3)) with molecular weight of 524 5% by mass and dipentaerythritol hexaacrylate (DPHA(a3 -4)) Mixture of 45% by mass) 2500 parts by mass and Neostan U-810 0.1 mass After the liquid temperature reached 50°C, 224 parts by mass of Desmodur I was added from the dropping funnel for 30 minutes. After the temperature rise subsided, the mixture was heated to 80°C and reacted for 3 hours. After confirming that the peak of the isocyanate group disappeared at 100°C, the temperature was lowered to room temperature and In the volatile matter, a urethane acrylate having a molecular weight of 1300 and 10 acryloyl groups (a2 -2) 46.7% by mass, dipentaerythritol pentaacrylate (a3-3) (DP PA, acryloyl group equivalent 105) 12.0 mass%, and dipentaerythritol hexahydrate A urethane acrylate mixture containing 41.3% by mass of sacryl (a3-4) (DPHA) A combined liquid (Q2) was obtained.

[0092] The materials used in the examples and comparative examples are described below.

[0093] <Polyfunctional urethane (meth)acrylate (a1)> (a1-1): molecular weight 1600, number of acryloyl groups 9 (a1-2): molecular weight 1400, number of acryloyl groups 9 (a1-3): molecular weight 4000, number of acryloyl groups 6 <Polyfunctional urethane (meth)acrylate (a2)> (a2-1): molecular weight 900, number of acryloyl groups 6 (a2-2): molecular weight 1300, 10 acryloyl groups <Polyfunctional (meth)acrylate (a3)> (a3-1): Pentaerythritol triacrylate (PE-3A) (a3-2): Pentaerythritol tetraacrylate (PE-4A) (a3-3): Dipentaerythritol pentaacrylate (DPPA) (a3-4): Dipentaerythritol hexaacrylate (DPHA) Multifunctional acrylate liquid (R1): Aronix M-403 (Zipene) manufactured by Toagosei Co., Ltd. Taerythritol pentaacrylate (a3-3) 55% and dipentaerythritol hexaacrylate Acrylate (a3-4) 45% mixture) Multifunctional acrylate liquid (R2): Arkema Co., Ltd.: SARTOMER SR368 ( Molecular weight 423, number of acryloyl groups 3, (a3-5)) Multifunctional acrylate liquid (R3): Negami Chemical Industries Co., Ltd.: Art Resin UN-5507 (part Molecular weight 17000, acryloyl group number 15.5, (a3-6), PGMAC (propylene glycol) Recall Monomethyl Ether Acetate (50% content)

[0094] <Preparation of blue pigment for dispersion> Blue pigment CI Pigment Blue 15:6 (Toyo Color Co., Ltd. "Lionol Blue" 100 parts of ES), 800 parts of ground salt, and 100 parts of diethylene glycol were mixed together in a stearyl alcohol flask. The mixture was charged into a 1-gallon kneader (manufactured by Inoue Seisakusho) and kneaded at 70°C for 12 hours. Add the mixture to 3,000 parts of warm water and mix it in a high-speed mixer for about 1 minute while heating it to about 70°C. The mixture was stirred for 8 hours to form a slurry, which was then filtered and washed repeatedly to remove salt and the solvent. After drying at 0°C for 24 hours, 98 parts of a finely divided blue pigment (BP) was obtained. The uniform primary particle size was 28.3 nm.

[0095] <Preparation of blue pigment dispersion (dB)> The following mixture was stirred until homogeneous, and then mixed with 0.5 mm diameter zirconia beads. Using an Eiger mill (Eiger Japan "Mini Model M-250MKII") After dispersing for 5 hours, the pigment dispersion was filtered through a 5.0 μm filter to obtain a pigment dispersion. Non-volatile content 20% due to PGMAc (propylene glycol monomethyl ether acetate) The dB was obtained by adjusting the mass percentage. Blue fine pigment (BP): 11.1 parts by weight Dispersant (Ajisper PB821, manufactured by Ajinomoto Fine Techno, DS): 12.1 parts by weight Propylene glycol monomethyl ether acetate: 76.8 parts by weight The average dispersed particle size (D50) of the resulting dispersion was 55 nm.

[0096] <Preparation of purple pigment for dispersion> Purple pigment CI Pigment Violet 23 (manufactured by Toyo Color Co., Ltd. "LIONOGE 100 parts of N VIOLET FG-6140), 800 parts of ground salt, and 100 parts of ethylene glycol was placed in a stainless steel 1-gallon kneader (manufactured by Inoue Seisakusho) and mixed for 7 minutes. The mixture was mixed at 0°C for 12 hours. The mixture was added to 3,000 parts of warm water and heated to about 70°C. Then, mix it in a high-speed mixer for about an hour to make a slurry, then filter and wash it with water repeatedly. After removing the salt and solvent, dry at 80°C for 24 hours and add 95 parts of violet fine pigment (VP). The volume average primary particle diameter of the resulting pigment was 53.7 nm.

[0097] <Preparation of purple dispersion (dV)> The following mixture was stirred until homogeneous, and then mixed with 0.5 mm diameter zirconia beads. Using an Eiger mill (Eiger Japan "Mini Model M-250 MKII") After dispersing for 3 hours, the mixture was filtered through a filter having a pore size of 5.0 μm to obtain a pigment dispersion. The body is treated with PGMAc (propylene glycol monomethyl ether acetate) to reduce non-volatile matter. The concentration was adjusted to 20% by mass to prepare a violet dispersion (dV). Purple micronized pigment (VP): 14.0 parts Dispersant (Ajisper PB821, manufactured by Ajinomoto Fine Techno, DS): 10.1 parts by weight Propylene glycol monomethyl ether acetate (PGMAc) :75.9 copies The average dispersed particle size (D50) of the resulting dispersion was 100 nm.

[0098] <Preparation of red pigment for dispersion> CI Pigment Red 254 (BASF "S3610CF") 200 parts, chloride 1400 parts sodium and 360 parts diethylene glycol in a 1-gallon stainless steel flask. The mixture was then placed in a mixing bowl (manufactured by Inoue Seisakusho) and kneaded at 80°C for 6 hours. The mixture is poured into hot water at 80°C and stirred for 2 hours to form a slurry, which is then filtered and washed with water. After repeatedly removing sodium chloride and diethylene glycol, dry at 85°C overnight. As a result, 190 parts of red fine pigment (RP) was obtained. The volume average primary particle diameter was 27.6 nm. I did.

[0099] <Preparation of red pigment dispersion (dR)> The following mixture was stirred until homogeneous, and then mixed with 0.5 mm diameter zirconia beads. Using an Eiger mill (Eiger Japan "Mini Model M-250MKII") After dispersing for 5 hours, the mixture was filtered through a 5.0 μm filter to obtain a pigment dispersion. Non-volatile content of 20% due to GMAc (propylene glycol monomethyl ether acetate) % by volume to prepare a red pigment dispersion (dR). Red fine pigment (RP): 14.4 parts Dispersant (Ajisper PB821, manufactured by Ajinomoto Fine Techno, DS): 10.1 parts Propylene glycol monomethyl ether acetate: 75.5 parts The average dispersed particle diameter (D50) of the resulting dispersion was 50 nm.

[0100] <UV protection agent (B)> UV protection agent (b-1): BASF: UVINUL 3050: Benzophenone UV protection agent

[0101] <Photopolymerization initiator (C)> (c-1): BASF Ltd.: Irgacure OXE03: Oxime ester type derivative (c-2): BASF Ltd.: Irgacure OXE01: Oxime ester type derivative (c-3): IGM Resins BV: ESACURE ONE: Oligo[2 -Hydroxy-2-methyl-[1-(methylvinyl)phenyl]propanone

[0102] <Solvent (E)> (e-1): Butyl acetate (manufactured by Sankyo Chemical Co., Ltd.) (e-2): MEK (methyl ethyl ketone, manufactured by Taishin Chemical Co., Ltd.) (e-3): PGM (propylene glycol monomethyl ether, manufactured by Taishin Chemical Co., Ltd.) (e-4): PGMAC (propylene glycol monomethyl ether acetate, Sankyo Chemical Industry Co., Ltd.) (e-5): DMC (dimethyl carbonate, manufactured by UBE Corporation) (e-6): MIBK (Methyl isobutyl ketone, manufactured by Mitsubishi Chemical Corporation)

[0103] <Example 1> In a flask equipped with a stirrer, 21.4 parts of urethane acrylate liquid (P1), Rate liquid (Q1) 67.9 parts, multifunctional acrylate liquid (R1) 14.2 parts, UV protection Agent UVINUL3050(b-1) 10.0 parts, photopolymerization initiator Irugacure OX E03(c-1) 10.0 parts, methyl ethyl ketone (e-2) 76.7 parts, propylene Glycol monomethyl ether (E-3) 20.0 parts, color tone adjuster blue pigment dispersion (D Add 0.176 parts of -B) and 0.418 parts of purple pigment dispersion (dV), stir and mix, and A composition for forming a hard coat layer containing the above compound was obtained. Urethane acrylate (a1-1): 14.0 parts Urethane acrylate (a2-1): 56.0 parts Pentaerythritol triacrylate (a3-1): 6.6 parts Pentaerythritol tetraacrylate (a3-2): 9.2 parts Dipentaerythritol pentaacrylate (a3-3): 7.8 parts Dipentaerythritol hexaacrylate (a3-4): 6.4 parts Total of active energy ray curing component (A) 100.0 parts Other non-volatile matter (f-1): 0.6 parts UV protection agent UVINUL3050(b-1): 10.0 parts Photopolymerization initiator Irgacure OXE03(c-1): 10.0 parts Blue micropigment (BP): 0.017 parts Purple micronized pigment (VP): 0.049 parts Dispersant (DS): 0.053 parts n-Butyl acetate (e-1): 2.8 parts Methyl ethyl ketone (MEK) (e-2): 76.7 parts Propylene glycol monomethyl ether (PGM) (e-3): 20.0 parts Propylene glycol monomethyl ether acetate (PGMAC) (e-4): 0.4 75 copies

[0104] <Examples 2 to 29 and Comparative Examples 1 to 7> As shown in Tables 1 to 3, the composition and the amount (parts by mass) were changed, but the composition was the same as in Example 1. In the same manner, the compositions for forming a hard coat layer of Examples 2 to 29 and Comparative Examples 1 to 7 were prepared. Ta.

[0105] The obtained composition for forming a hard coat layer was used to measure the transmittance, a * , b * ,lead The pen hardness, adhesion, warping, and white color clarity were evaluated. The results are shown in Tables 1 to 3.

[0106] [Transmittance measurement] A 50μm thick light-transmitting film (easily adhesive PET film) with a transmittance of 80% or more at 380nm. The obtained composition for forming a hard coat layer was applied onto a film (Lumirror U403 manufactured by Toray Industries, Inc.). The composition was applied using a bar coater No. 9, and then dried in a hot air oven at 100°C for 2 minutes. , 400mJ / cm UV radiation from a high-pressure mercury lamp with an output of 80w / cm 2 Irradiate and harden the coating layer. The resulting mixture is then cured to obtain a light-transmitting film and a hard-coat film having a hard-coat layer. Ta. The hard coat film having the hard coat layer was heated at 23° C. and a relative humidity of 50% (hereinafter referred to as 5 The Hitachi High-Tech spectrophotometer U-4100 was installed in a constant temperature and humidity room at 100°C (0% RH). The transmittance at 380 nm and 420 nm was measured using a FT-IR spectrophotometer.

[0107] [a * , b * Measurement of [Transmittance measurement] * , b * A hard coat film for measurement was obtained. The SH spectrometer haze meter (manufactured by Nippon Denshoku Industries Co., Ltd.) was installed in a constant temperature and humidity room at 0% RH. 7000" and the average value of n=3 measurements under D65 light source is a * , b * It was decided.

[0108] [Pencil hardness] In the same manner as in [Transmittance Measurement], a hard-coated film for evaluating pencil hardness was obtained. The coated film was cut into test films of 100 mm length x 50 mm width. This was used as a test film. The pencil hardness of the obtained hard coat film was measured using pencils of different hardness according to JIS K54 The measurements were performed using a test method conforming to 00 (1990). ◎: Pencil hardness is 3H or more (excellent) ○: Pencil hardness is H~2H (good) △: Pencil hardness is F (no problem in practical use) ×: Pencil hardness is HB or less (not practical)

[0109] [Adhesion] In the same manner as in [Transmittance Measurement], a hard coat film for evaluating adhesion was obtained. The opposite side of the coated film on which the hard coat layer was formed was attached to a glass plate with a thickness of about 20 μm. After pasting via the adhesive layer, the hard coat layer surface is A cross-cut peel test was carried out and judged according to the following criteria. ◎: Peeling count 0 / 100 (Excellent) ○: Peeling count 1-5 / 100 (good) △: Number of peeled off pieces: 6-20 / 100 (no practical problems) ×: Number of peeled pieces: 21-100 / 100 (not practical)

[0110] [Warp test] A hard coat film for warpage test was obtained in the same manner as in [Transmittance Measurement]. The obtained hard-coated film was cut into a length of 100 mm and a width of 50 mm to prepare a test film. The mixture was then left in a temperature and humidity chamber at 22°C and 50% RH for 6 hours. Place the test film on a horizontal surface and measure both ends of the long side and three points in the center. The distance between the ends was measured using a microgauge and the average value was calculated. ◎: 40mm or more (excellent) ○: 30mm or more and less than 40mm (good) △: 10mm or more and less than 30mm (no practical problems) ×: Cylindrical or less than 10 mm (not practical)

[0111] [White clarity evaluation] In the same manner as in [Transmittance Measurement], a hard coat film for evaluating white color clarity was obtained. The hard coat layer of the obtained hard coat film was placed on the Konica Minolta Calibration plate for colorimeter manufactured by Epson Corporation (CIE Y=94.9, x=0.31 35, y=0.3205, hereafter referred to as the standard plate) and visually check the difference in color with the standard plate. The evaluation was performed according to the following criteria. ◎: No noticeable difference in color compared to the standard plate (Excellent) ○: Slightly tinted compared to the standard plate (good) △: The color is clearly different from the standard plate, but the color of the standard plate can be confirmed (no practical problem) death) ×: The color is too dark to see the color of the standard plate (not practical)

[0112] [Table 1]

[0113] [Table 2]

[0114] [Table 3]

[0115] As shown in Tables 1 to 3, the use of the hard coating agent of the present invention provides high ultraviolet ray blocking properties. It protects the display from UV rays from the outside, improves white clarity, and reduces color distortion. Improved display production process efficiency due to its high hard coat properties and high display hard coat properties Hard coat film having a hard coat layer that is scratch-resistant during the production process We can provide you with a room.

Claims

1. A composition for forming a hard coat layer on a light-transmitting film, comprising: Active energy ray curable component (A), UV cutter (B), photopolymerization initiator (C), color Contains a conditioning agent (D) and a solvent (E), The active energy ray-curable component (A) has 6 or more (meth)acryloyl groups, and a polyfunctional urethane (meth)acrylate (a1) having a nurate ring skeleton, The photopolymerization initiator (C) is an active ingredient for forming a hard coat layer, which contains an oxime ester derivative. Energy ray curable composition.

2. The active energy ray curable component (A) is Further, the compound has 4 to 15 (meth)acryloyl groups and a weight average molecular weight of 50 Polyfunctional urethane (meth)acrylate having a molecular weight of 0 to 15,000 (excluding (a1)) The hard coat composition according to claim 1, which comprises (a2) and another polyfunctional (meth)acrylate (a3). An active energy ray-curable composition for forming a coating layer.

3. The active energy ray-curable composition for forming a hard coat layer according to claim 1 is applied onto a light-transmitting film. The hard coat film has a hard coat layer formed by curing a composition.

4. The transmittance (ta) at a wavelength of 380 nm is 3% or less, and the transmittance at a wavelength of 420 nm is 4. The hard coat film according to claim 3, wherein the thickness ratio (tb) is 65% or more.

5. L * a * b * In the color system, b * 5. The method according to claim 4, wherein the Hard coated film.

6. L * a * b * In the color system, a * is -2.5 or more and 1.5 or less according to claim 5. Hard coat film.

7. A laminate comprising the hard coat film according to any one of claims 3 to 6 and another functional layer. Optical laminated electronic devices.

Citation Information

Patent Citations

  • Hard coat film having ultraviolet absorptivity

    JP2009006513A

  • Surface protection film

    JP2016107498A